Cryptocurrency - Illusion vs Solution - et. al., Aida Wijaya, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The pros and cons regarding the use of cryptocurrency in supporting or - in the extreem – replacing conventional currency (fiat) is still going on. More than 2 decades of its born, still there are more government in the cons position than in favor of the use of cryptocurrency. This paper explored the cryptocurrency as to be one of many aspects in deciding whether it would be positioned as an illusion or to be a solution for a nation’s economy. This paper also portrait cryptocurrency from the accounting point of view. As the financial information provider, accounting is important for fundamental decisions in economy because of its nature to be conservative. The ultimate goal is that this could be one of many sources to help Indonesian government in deciding how to best deal with cryptocurrency.